The patient acceptability of a remotely delivered pain management programme for people with persistent musculoskeletal pain: A qualitative evaluation. Issue 6 (December 2022) - Booth, Gregory; Zala, Sonia; Mitchell, Chloe; Zarnegar, Roxaneh; Lucas, Andrew; Gilbert, Anthony W
Introduction: Remotely delivered pain management programmes have been offered in place of in-person programmes by many chronic pain services since the onset of the COVID-19 pandemic. There is a lack of evidence regarding the acceptability of these programmes. In this evaluation, we have explored patients' acceptability of a remotely delivered pain management programme for patients with persistent musculoskeletal pain. Methods: Qualitative data were collected using focus groups with participants who had previously attended the remote pain management programme. Data were analysed using abductive analysis. Results: Three focus groups were conducted with a total of 13 participants. The programmme was either entirely acceptable, had some acceptable components or was not acceptable to patients. Factors leading to the programme being acceptable include learning to manage pain from home, receiving high quality care from home, enhancing the potential of rehabilitation using technology, enabling attendance on a pain management programme from home, overcoming social distancing requirements of COVID-19 using technology, and virtual peer support. Factors leading to the programme not being acceptable include having an inappropriate home environment for virtual therapy, communication challenges with virtual therapy, technological issues and concerns regarding the quality of care. Conclusions: There is a spectrum of acceptability with respect to the remote programme. The factors that influence this are dynamic, individual and situational. Hybrid programmes have the potential to enhance access to pain management programmes and improve patient experience and programme outcomes in the future.